PROCESS FLUIDS FOR RECOVERING IMPERMEABILITY OF WELL ANNULUS OF SUBMERGED RESERVOIRS IN ROCK-SALT - Alla A. Pereima (Вестник Северо-Кавказского федерального университета, 2022)
When operated long-term, wells for underground gas storage in rock-salt show corrosive wear in the casings, as well as disturbed insulating capacity in the annulus, which results in need for repair works. The article contains description of the process fluids used to repair rock-salt submerged reservoirs.